Prospects and challenges of composites production from wood-based residue as utilisation-based approach for nigeria forest resources sustainability (2022)
Generations of supplementary raw materials in form of composites from wood waste residue offer opportunities for reducing exploitation pressure on forest resources. For coordination and impact measurement however, there is need to document information of the prospects and challenges of adopting this sustainability measure to effectively harness the approach to mitigate the effects of climate change and forest resources supply shortage. This study examines the grey areas, limiting it to prospects and challenges, of adopting the aforementioned technique in Nigeria. A review of related literature on predominant wood waste sources and composite products were carried out. Local sources and nature of wood waste in Nigeria were also identified through the secondary data. Information revealed that most wood wastes used for composites are directly sourced from forests (30.43%) while the least source is from old household furniture (4.35%). This perhaps is an indication that wood wastes generated in the forest exceed those generated at other locations. Reconstituted wood composites are the most common wood waste composite products (66.67%) that have been adopted in Nigeria. Reasons are largely due to nature of wood wastes and technological capacity. The feasibility of this approach is reliant on investment in industry by local manufacture of composite processing equipment and facilities, as well as creating an environment that is conducive for the industry to thrive.